Finite element method using vector finite elements applied to eddy current problems - Adams, Leila (Department of Electrical Engineering, 2014)
Vector fields found in electromagnetics are fundamentally different to vector fields found in other research areas such as structural mechanics. Electromagnetic vector fields possess different physical behaviour patterns and different properties in comparison to the other vector fields and therein lies the necessity of the development of a finite element which would be able to cater for these differences . The vector finite element was then developed and used within the finite element method specifically for the approximation of electromagnetic problems. This dissertation investigates the partial differential equation that governs eddy current behaviour. A finite element algorithm is coded and used to solve this partial differential equation and produce vector field simulations for fundamental eddy current problems.